A global database of Holocene paleotemperature records - Kaufman, Darrell; McKay, Nicholas; Routson, Cody; Erb, Michael; Davis, Basil; Heiri, Oliver; Jaccard, Samuel; Tierney, Jessica; Datwyler, Christoph; Axford, Yarrow; Brussel, Thomas; Cartapanis, Olivier; et al. (Scientific data, 2020)
A comprehensive database of paleoclimate records is needed to place recent warming into the longer-term context of natural climate variability. We present a global compilation of quality-controlled, published, temperature-sensitive proxy records extending back 12,000 years through the Holocene. Data were compiled from 679 sites where time series cover at least 4000 years, are resolved at sub-millennial scale (median spacing of 400 years or finer) and have at least one age control point every 3000 years, with cut-off values slackened in data-sparse regions. The data derive from lake sediment (51%), marine sediment (31%), peat (11%), glacier ice (3%), and other natural archives. The database contains 1319 records, including 157 from the Southern Hemisphere. The multi-proxy database comprises paleotemperature time series based on ecological assemblages, as well as biophysical and geochemical indicators that reflect mean annual or seasonal temperatures, as encoded in the database. This database can be used to reconstruct the spatiotemporal evolution of Holocene temperature at global to regional scales, and is publicly available in Linked Paleo Data (LiPD) format. Measurement(s)climateTechnology Type(s)digital curationFactor Type(s)temporal interval center dot geographic location center dot proxy typeSample Characteristic - Environmentclimate systemSample Characteristic - LocationEarth (planet) Machine-accessible metadata file describing the reported data:
Gesehen am 22.07.2020